Give Birth Without Pain With The Rebozo Technique - Farida, Siti; Isnida Ismail, Nor; Kartika Hayu Asri, Novia (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
Labor pain is caused by contractions of the uterus. Unanticipated labor pain can cause psychological and cardiovascular impacts, namely increased fear and anxiety, cardiac output, blood pressure, pulse and impact on the fetus, namely acidosis due to hypoxia. The rebozo technique is a non-pharmacological therapy to speed up the opening of the cervix of the birth mother by rhythmically shaking the pelvis using the rebozo. The gentle movements in the rebozo technique really help the birthing mother feel more comfortable, triggering the release of the hormone oxytocin and endorphin hormones, thereby facilitating the birthing process. This research was conducted by comparing labor pain before and after being given the rebozo technique (Pre-experimental Design with One GroupPretest-Posttest Design) to 13 mothers who met the inclusion criteria. The statistical test results obtained a p-value of 0.001 so it can be concluded that after carrying out the rebozo technique for 5 -10 minutes in the first stage of labor it can relax the body, reduce anxiety levels, speed up the labor process, reduce the intensity of labor pain. The rebozo technique is an alternative that can make birthing mothers feel the direct participation carried out by midwives so that it can have positive psychological and clinical implications.